2020
DOI: 10.2355/isijinternational.isijint-2020-149
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Twin-roll Casting Process for Complex Section Products

Abstract: Complex section products have significant lightweight and functional characteristics, and the twin-roll casting (TRC) is characterized by high efficiency and short flow. Hence, the TRC process for fabricating complex section products combines both advantages and will have a broader market demand and application prospect. In this paper, the research progress in recent years is reviewed, and novel TRC processes are divided into three categories according to the product section characteristics, namely transverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Aluminum alloys with the addition of elements such as Ce and La (REM) are often used [3 -10] for electrical products. Traditional technologies for their production by extrusion cast billets and subsequent drawing are increasingly being replaced by continuous extrusion methods (Conform, CRE) and combined processing (Castex, combined casting with rolling-extrusion, ingotless rolling-extrusion, casting-rolling) [11,12]. The development of one of these scientific areas related to the creation of technologies for producing wire for electrical purposes from aluminum alloys of various alloying systems by combined processing methods is being carried out by scientists from Siberian Federal University (SFU).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum alloys with the addition of elements such as Ce and La (REM) are often used [3 -10] for electrical products. Traditional technologies for their production by extrusion cast billets and subsequent drawing are increasingly being replaced by continuous extrusion methods (Conform, CRE) and combined processing (Castex, combined casting with rolling-extrusion, ingotless rolling-extrusion, casting-rolling) [11,12]. The development of one of these scientific areas related to the creation of technologies for producing wire for electrical purposes from aluminum alloys of various alloying systems by combined processing methods is being carried out by scientists from Siberian Federal University (SFU).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, recently, in order to obtain longish semi-finished products from aluminum alloys technologies have been developed for continuous casting of ingots of small cross-section into an electromagnetic mold (EMM) and their subsequent deformation on installations for continuous extrusion Conform [61,62] or combined rolling-extruding (CRE) [60,[63][64][65] and drawing [4,[22][23][24][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. The use of such technologies can lead to the solution of these issues and the production of small-diameter wire with the required set of operational properties.…”
Section: Introductionmentioning
confidence: 99%
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%